Why are acute ischemic stroke patients not receiving thrombolysis in a telestroke network?. (July 2020) - Nalleballe, Krishna; Sharma, Rohan; Kovvuru, Sukanthi; Brown, Aliza; Sheng, Sen; Gundapaneni, Sukumar; Ranabothu, Saritha; Veerapaneni, Poornachand; Joiner, Renee; Kapoor, Nidhi; Culp, William; Onteddu, Sanjeeva
Objective: The purpose of this study was to determine reasons for not giving intravenous tissue plasminogen activator to eligible patients with acute ischemic stroke in a telestroke network. Methods: We performed a retrospective analysis of prospectively collected data of patients who were seen as a telestroke consultation during 2015 and 2016 with the Arkansas Stroke Assistance through Virtual Emergency Support programme for possible acute ischemic stroke. Results: Total consultations seen were 809 in 2015 and 744 in 2016, out of which 238 patients in 2015 and 247 patients in 2016 received intravenous tissue plasminogen activator. In 2015 and 2016, out of the remaining 571 and 497 patients, 294 and 200 patients respectively were thought to be cases of acute stroke based on clinical evaluation. The most common reasons for not being treated in 2015 and 2016, respectively, were; (a) minimal deficits in 42.17% and 49.5% cases, (b) falling out of the 4.5-hour time window in 22.44% and 22% cases, (c) patient/next of kin refusal in 18.02% and 16.5% cases. Less common reasons included limited functional status, abnormal labs (thrombocytopenia, elevated international normalised ratio (INR)/prothrombin time (PT)/partial thromboplastin time (PTT), hypo or hyperglycemia etc), recent surgery and symptoms being too severe etc. Conclusion: 'Minimal deficits' and 'out of time window' continue to be the major causes for not receiving thrombolysis during acute ischemic stroke in both traditional and telestroke systems. Patient/next of kin refusal was high in our telestroke system when compared to traditional practices. Considering the increasing utility of telestroke this needs to be further looked into, along with the ways to address it.